2016
DOI: 10.1007/s12011-016-0891-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Trace Element Levels and Superoxide Dismutase Activity in Patients with Inflammatory Bowel Disease: Translating Basic Research into Clinical Application

Abstract: The relationship of minerals and trace elements with inflammatory bowel disease (IBD) is complex. Alterations in their metabolism can be induced by the diseases and their complications. To study the role of trace elements in IBD patients' serum zinc and copper and their related enzymes, including superoxide dismutase (SOD), activity were measured in patients with IBD patients as well as in healthy subjects. In addition, the correlation between serum trace element levels, albumin, total protein, urea level, cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 36 publications
3
41
0
1
Order By: Relevance
“…The serum trace element levels and superoxide dismutase activity in patients with IBD changes, compared to the healthy controls (28). In addition, use of antioxidants is an important complementary treatment in cardiometabolic, neurological, and gastrointestinal disorders (29), such as ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The serum trace element levels and superoxide dismutase activity in patients with IBD changes, compared to the healthy controls (28). In addition, use of antioxidants is an important complementary treatment in cardiometabolic, neurological, and gastrointestinal disorders (29), such as ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of nitric oxide are thought to be physiological and protective, whereas its high levels as proinflammatory and injurious [ 32 ]. Recently, in CD patients, the overexpression of ROS and NO, as well as lower concentrations of numerous antioxidants, have been studied in intestinal mucosa or blood but not in saliva [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that MPO expression in the intestinal mucosa is positively correlated with the severity of intestinal inflammation in UC, which can be used as a monitoring index for disease severity in UC patients [29]. MPO is abundant in neutrophils, which use hydrogen peroxide as an oxidant to oxidize tyrosine to tyrosyl.…”
Section: Logistic Regression Analysismentioning
confidence: 99%